2002
DOI: 10.1051/vetres:2002008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bartonella infection in domestic cats in Denmark

Abstract: -Whole blood and serum from 93 cats (44 pets and 49 shelter/stray cats) from Denmark were tested for the presence of feline Bartonella species by culture and for the presence of Bartonella antibodies by serology. Bartonella henselae was isolated from 21 (22.6%) cats. Bacteremia prevalence was not statistically different between shelter/stray cats (13/49, 26.5%) and pet cats (8/44, 18.2%), but varied widely by geographical origin of the cats, even after stratification for cat origin or age (p < 0.001). All isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
3
24
2
Order By: Relevance
“…Recognized as the main cause of cat scratch disease in humans (Chomel 2000), Bartonella henselae has been reported in wild felids, arctic foxes (Vulpes lagopus), mongooses (Herpestes auropunctatus), and palm civets (Paguma larvata) (Sato et al 2013) in addition to the well-known domestic cat hosts (Chomel et al 2002). Two more Bartonella species associated with domestic cats and recognized as human pathogens (Bartonella clarridgeiae and Bartonella koehlerae) have also been reported in wild animals (Kaewmongkol et al 2011;Hwang and Gottdenker 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recognized as the main cause of cat scratch disease in humans (Chomel 2000), Bartonella henselae has been reported in wild felids, arctic foxes (Vulpes lagopus), mongooses (Herpestes auropunctatus), and palm civets (Paguma larvata) (Sato et al 2013) in addition to the well-known domestic cat hosts (Chomel et al 2002). Two more Bartonella species associated with domestic cats and recognized as human pathogens (Bartonella clarridgeiae and Bartonella koehlerae) have also been reported in wild animals (Kaewmongkol et al 2011;Hwang and Gottdenker 2013).…”
Section: Introductionmentioning
confidence: 99%
“…seroprevalence is higher in hot and humid climates [16] . In healthy pet cats, Bartonella henselae seroprevalence has been reported to be 17% in Thailand [17] ; 9.6-19.6% in China [18] ; 32% in Jordan [19] ; 44.2% in Denmark [20] ; and 54% in Indonesia/Jakarta [21] . In a pilot study carried out in healthy cats in Brasil, Bartonella henselae prevalence was found to be 47.5% and it was stressed that performing this study in the whole region to include larger populations of animals was very important for human and animal health [22] .…”
Section: Discussionmentioning
confidence: 99%
“…In the Czech Republic, while the total prevalence was 8% in a study including stray cats and cats in an animal shelter, bacteriaemia prevalence was determined to be 67% in stray cats and 5% in cats in the animal shelter [26] . [20] . In Algeria, Bartonella henselae seroprevalence was found to be 17% in stray cats [27] .…”
Section: Discussionmentioning
confidence: 99%
“…berkhoffii (ATCC 51672), B. henselae (ATCC 49882) and B. clarridgeiae (Ankara stray cat strain). DNA extraction from the isolates and the control strains was carried out as described by Chomel et al [13].…”
Section: Methodsmentioning
confidence: 99%